Fertility patients under COVID-19: attitudes, perceptions and psychological reactions. Issue 12 (13th November 2020) - Ben-Kimhy, Reut; Youngster, Michal; Medina-Artom, Tamar R; Avraham, Sarit; Gat, Itai; Marom Haham, Lilach; Hourvitz, Ariel; Kedem, Alon
Abstract: STUDY QUESTION: What are the perceptions of infertility patients and the factors correlating with their psychological distress, following suspension of fertility treatments during the Corona Virus Disease-19 (COVID-19) pandemic? SUMMARY ANSWER: Most patients preferred to resume treatment given the chance regardless of background characteristics; higher self-mastery and greater perceived social support were associated with lower distress, while feeling helpless was associated with higher distress. WHAT IS KNOWN ALREADY: Infertility diagnosis and treatment frequently result in significant psychological distress. Recently published data have shown that clinic closure during the COVID-19 pandemic was associated with a sharp increase in the prevalence of anxiety and depression among infertile patients undergoing IVF and was perceived as an uncontrollable and stressful event. Personal resources play an important protective role in times of crisis, helping reduce levels of distress. STUDY DESIGN, SIZE, DURATION: This cross-sectional questionnaire study included patients whose fertility treatment was suspended following the COVID-19 pandemic, in a tertiary hospital. The survey was delivered to 297 patients within 12 days at the beginning of April 2020. PARTICIPANTS/MATERIALS, SETTING, METHODS: The self-administered questionnaire included items addressing: (i) patients' demographic characteristics, (ii) anxiety related to COVID-19 infection risk and level of social support, (iii) patients' perceptions of the new guidelines and description of subsequently related emotions and (iv) two validated scales assessing levels of emotional distress and self-mastery. Multivariate analysis was conducted to assess factors alleviating or increasing emotional distress during the COVID-19 pandemic. MAIN RESULTS AND THE ROLE OF CHANCE: There were 168 patients who completed the survey, giving a response rate of 57%. Study variables in the regression model explained 38.9% of the variance in psychological distress experienced by patients during treatment suspension. None of the background characteristics (e.g. age, marital status, parity, economic level or duration of treatments) had a significant contribution. Feeling helpless following the suspension of treatments was associated with higher distress ( P < 0.01). Higher self-mastery and greater perceived social support were associated with lower distress ( P < 0.01). Despite the ministry of health's decision, 72% of patients wished to resume treatment at the time of survey. LIMITATIONS, REASONS FOR CAUTION: This was a cross-sectional study, thus information about patients' characteristics prior to the COVID-19 pandemic was not available. The length and implications of this pandemic are unknown. Therefore, the ability to draw conclusions about the psychological consequences of the crisis is limited at this point of time. WIDER IMPLICATIONS OF THE FINDINGS: Personal resources play an important protective role in times of crisis, helping to reduce levels of distress. Study findings suggest that attention should be paid to strengthening and empowering patients' personal resources together with directly confronting and containing feelings of helplessness. In line with the European Society for Human Reproduction and Embryology (ESHRE) guidelines, especially at this time of high levels of distress, it is imperative to offer emotional support to reduce stress and concerns. Furthermore, as the pandemic is stabilizing, resumption of treatment should be considered as soon as appropriate according to local conditions. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by the IVF unit of the Shamir Medical Center. All authors declare no conflicts of interest. TRIAL REGISTRATION NUMBER: N/A